2015
DOI: 10.1016/j.bbmt.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol for the Prevention of Graft-versus-Host-Disease after Allogeneic Hematopoietic Cell Transplantation: Results of a Phase II Study

Abstract: Graft-versus-host-disease (GVHD) is a major obstacle to successful allogeneic hematopoietic cell transplantation (alloHCT). Cannabidiol (CBD), a nonpsychotropic ingredient of Cannabis sativa, possesses potent anti-inflammatory and immunosuppressive properties. We hypothesized that CBD may decrease GVHD incidence and severity after alloHCT. We conducted a phase II study. GVHD prophylaxis consisted of cyclosporine and a short course of methotrexate. Patients transplanted from an unrelated donor were given low-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Lastly, it was found that doses of 5 mg/kg/d prevented occurrence of graft‐ vs ‐host disease in a phase II clinical trial ( n = 48) and 5–10 mg/kg/d doses have been shown in a case report to remove withdrawal symptoms from a patient with cannabis dependency …”
Section: Resultsmentioning
confidence: 99%
“…Lastly, it was found that doses of 5 mg/kg/d prevented occurrence of graft‐ vs ‐host disease in a phase II clinical trial ( n = 48) and 5–10 mg/kg/d doses have been shown in a case report to remove withdrawal symptoms from a patient with cannabis dependency …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, CBD has been suggested as a promising treatment also for autoimmune myocarditis and possibly other autoimmune disorders, and it might be useful for organ transplantation (466). Very recently, the positive results of a phase II study that assessed the safety and efficacy of CBD in the prevention of acute graft-versus-host-disease were reported (931).…”
Section: Pain Inflammation Autoimmunity and Retinal Diseasesmentioning
confidence: 99%
“…However, Δ9‐THC administration was associated with side effects including drowsiness, dizziness, ataxia, and blurred vision. In a multicenter, double‐blind, placebo‐controlled study, THC:CBD extract and Δ9‐THC extract alone were also effective for management of pain resistant to strong opioids . Cannabinoid use for pain management has also been evaluated in a few clinical studies, especially for the treatment of both neuropathic and chronic rheumatic pain.…”
Section: Cannabinoids As Potential Therapeutic Agentsmentioning
confidence: 99%